The impact of market orientation on NSD and financial performance of hospital industry - TARIM, MEHVEŞ (EMERALD GROUP PUBLISHING LTD, 2008)
Purpose - The principal aim of this study is to determine the critical factors of market orientation (MO) and to measure its effect on new service development (NSD) and financial performance of hospital industry in Turkey. Design/methodology/approach - Drawing on a self-administered questionnaire, the data were collected from a sample of privately-held general hospitals within the city of Istanbul in Turkey. Based on theoretical considerations, a model was proposed to examine the interrelationships among MO, NSD-performance and financial performance. Findings - Data analysis reveals that while MO has a strong and positive effect on NSD-performance, it has no significant effect on financial performance. Also a strong and positive relationship was noted between NSD-performance and financial performance. Finally, the findings also provided evidence for the mediating role of NSD-performance in. the relationship between MO and financial performance in the hospital industry. Research limitations/implications - First, due to relatively small sample size, a caution should be exercised when interpreting the results. Second, the data were collected from hospitals in Turkey, which may restrict to some extent generalizability of findings. Third, we relied on the subjective evaluations of senior, executives. It would therefore be useful to replicate the results with objective measures of performance indicators. Practical implications - Although there is compelling evidence that MO has a positive effect on business performance, it alone may not be able to produce superior performance. Many hospitals are committed to MO and new services development. The framework clearly indicates that a strong commitment to both the NSD-performance and marketing areas is essential for improving the financial performance of hospitals. Also, to remain competitive in today's healthcare industry, hospital managers should all keep pace with the daily changes in the market place and stay attuned to NSD activities and quality management practices. Originality/value - The main thrust of this study is to investigate whether the relationship between MO and financial performance is mediated by NSD-performance in hospital industry. This constitutes the novelty of this research as most prior empirical research investigating a mediating mechanism through which MID affects firm performance largely focused on other factors with no or little emphasis being placed on NSD activities or NSD-performance in healthcare context.
Keywords: market orientation; financial performance; hospitals; Turkey; INNOVATION; SERVICE; FAILURE; SUCCESS; DRIVEN; FIRMS; TQM